2014
DOI: 10.1007/s00455-014-9538-5
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Pressure During Swallowing in Adults with Down Syndrome and Its Relationship with Palatal Morphology

Abstract: In individuals with Down syndrome, hypotonicity of the tongue and an underdeveloped maxilla may lead to poor oral motor coordination, which adversely affects the oral phase of swallowing. This study aimed to evaluate the characteristics of pressure produced by the tongue against the hard palate during swallowing in individuals with Down syndrome. In addition, the relationship between tongue pressure and palatal morphology was examined. We studied nine adults with Down syndrome and ten healthy adults as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 39 publications
4
35
0
5
Order By: Relevance
“…These results corroborate those in the literature, which preconizes that both the anatomical changes and the neuromotor control of swallowing in this population may negatively affect deglutition (3,11) . Posterior oral spillage Presence of premature liquid escape to the hypopharynx, surpassing the region in which pharyngeal response should occur.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate those in the literature, which preconizes that both the anatomical changes and the neuromotor control of swallowing in this population may negatively affect deglutition (3,11) . Posterior oral spillage Presence of premature liquid escape to the hypopharynx, surpassing the region in which pharyngeal response should occur.…”
Section: Discussionsupporting
confidence: 91%
“…Aspiration of reflux content is common in the pediatric population diagnosed with GER (14) , generating complaints about gagging during feeding, which may be mistaken for oropharyngeal symptoms. However, it is relevant to conduct an objective investigation on swallowing in this population, considering that other studies with larger samples have already demonstrated higher frequency of laryngotracheal aspiration (2,3) .…”
Section: Pharyngeal Transit Timementioning
confidence: 99%
See 1 more Smart Citation
“…Despite various reported methods for evaluating the shape of the palate and dental arch, there is no consensus standard [44, 45]. In this study, palate height, narrowing of the dental arch, and the ratio of front area space were regarded as “palate and dental arch parameters,” which could be easily measured on maxillary stone models.…”
Section: Discussionmentioning
confidence: 99%
“…It is even associated with diseases like dysphagia, obstructive sleep apnea and malocclusions as well. The measurement of tongue pressure helps to evaluate the performance of tongue in resting state and functional movement, which has been widely applied in clinical research—tongue pressure and masticatory function in dysphagia patients; tongue pressure changes in patients with tongue cancer before and after resection and reconstruction; tongue pressure in adults with Down syndrome; tongue pressure of spinal and bulbar muscular atrophy patients, etc.…”
Section: Introductionmentioning
confidence: 99%